Development and validation of a gridded emissions inventory for HFC-134a in China - Jing Wu; Tong Wang; Minde An; Shan Ding; Bo Yao; Luke M. Western; Pallav Purohit; Zehua Liu; Zechen Zhang; Lin Peng (Environment International)
1,1,1,2-Tetrafluoroethane (HFC-134a), a potent greenhouse gas, breaks down to form trifluoroacetic acid (TFA). Lack of its gridded emissions inventories makes it difficult to analyze the spatial distribution of emissions. This study developed a framework for national and gridded HFC-134a bank and emission calculations, validation and environmental impact assessments. Within this framework, we used production and consumption data along with emission factors to compile a gridded inventory for China. The results reveal an increase in national HFC-134a emissions, from 0.1 kt yr−1 in 1995 to 48 kt yr−1 in 2020, with banks also increasing from 0.9 to 301 kt. Guangdong, Jiangsu, and Shandong provinces showed the largest cumulative emissions, totaling 98 kt between 1995 and 2020, representing 28% of HFC-134a national emissions. A Lagrangian dispersion model, in conjunction with atmospheric observations, was used to validate the gridded inventory, where the simulations based on the gridded inventory were in reasonable agreement with the observations. A carbon–neutral (CN) scenario was developed to project future emissions. The adoption of HFO-1234yf and R-513A as substitutes for HFC-134a is projected to cause an additional 701 kt of cumulative TFA formation potential between 1995 and 2060, on top of the 3825 kt projected under the Kigali Amendment scenario.